2011
DOI: 10.1002/hed.21656
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma in black thyroids

Abstract: The finding of a black thyroid gland is unusual and disconcerting. To our knowledge, this is the first study aimed at documenting the malignant potential of black thyroid glands. This report documents that the risk of malignancy is higher in black thyroid compared to non-black thyroid glands. Furthermore, among those with papillary thyroid cancer, the presence of the pigment did not correlate with malignancy, multifocality, or tumor size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…For example, Kandil and colleagues reported finding thyroid cancer in 65% of patients with black thyroid 4. The cancer most frequently associated with black thyroid is papillary thyroid cancer (PTC), which has been observed in 30 to 39% of black thyroid cases.…”
mentioning
confidence: 99%
“…For example, Kandil and colleagues reported finding thyroid cancer in 65% of patients with black thyroid 4. The cancer most frequently associated with black thyroid is papillary thyroid cancer (PTC), which has been observed in 30 to 39% of black thyroid cases.…”
mentioning
confidence: 99%
“…We previously reported in a smaller series that 65% (41/63) of the patients who presented with black thyroid glands were found to have thyroid malignancy [1], while Bruins et al [8 ]reported a smaller incidence rate (30%) of malignancy in black thyroid. Although the incidence rates of malignancy in patients with black thyroid glands in both of these studies are inconsistent, they show a clear association between black thyroid glands and thyroid cancer potential.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of thyroid carcinoma in black thyroid ranges from 30-65% [1,8]. There is a well-documented gender and racial disparity associated with thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations